The effect of soft skills on organizational performance: The mediating role of resilient leadership - Danang Sudarso Widya Prakoso Joyo Widakdo (Global Business & Finance Review (GBFR), 2022)
Purpose: This study aimed to examine the resilient leadership's ability to mediate the effect of workability, discipline, and communication or soft skills on organizational performance. Design/methodology/approach: This leadership performance assessment study used Structural Equation Modeling (SEM) applied to Organizational Behavior with case studies of State companies. Data were collected using in-depth interviews with regional leaders and online questionnaires distributed to participants from State-Owned Enterprises (BUMN) engaged in food logistics in the East Java Province, Indonesia. Findings: This study found a positive and significant effect of workability, discipline, and communication on leadership resilience and organizational performance mediated by leadership improvement. This showed that strong leader- ship increases the influence of soft skills on the company's organizational performance. Research limitations/implications: This study only assessed the organizational leaders' performance within the scope of the BULOG East Java Regional Office, meaning the research results cannot be generalized. It also tested the differences between samples by comparing the organizational performance of several companies' sectors. Originality/value: This study linked soft skills comprising workability, discipline, communication, and personality, with organizational performance mediated by tough leadership.
Keywords: 650; Human Resources; Indonesian Logistics Bureau; Organizational Behavior; Resilient; Soft-skills